Eficacia de tres herbicidas post-emergentes en el control de malezas en dos variedades de Haba (vicia faba l.) en la zona de Santa Martha de Cuba, provincia del Carchi - Cevallos Yandun, Willam Patricio (2015)
The investigation was carried out in Santa Martha of Cuba, canton Tulcán, Carchi province, in order to study the effectiveness of three post-emergent herbicides to the overgrowths control in the crop of two bean varieties (Vicia faba L.) The studied treatments were the varieties of beans (Semi green and Argentina) and the sub treatments herbicides products and the doses for liter (Oxifluorfen 1.25 cc/L, Pendimentalin 5 cc/L, Linuron 2.5g/L) and the absolute witness without application. During the investigation the Design of Divided Parcels (DPV) was used with two treatments, four sub treatments and three repetitions. The evaluated variables were: number of overgrowths at the 15; 60 and 45 dda, of the herbicides, effectiveness of the overgrowths at the 15; 30 and 45 dda, of the herbicides, days to the flowering, number of sheaths per plant, days to the crop, weight of green sheaths and yield in kg/ha. All determined variables were subjected to the variance analysis, using the Tukey test to 5%...........